Electronic phase transformations and energy gap variations in uniaxial and biaxial strained monolayer VS2 TMDs: A comprehensive DFT and beyond-DFT study - Orhan, Oguzhan; Ozonder, Sener; Ozgen, Soner (Elsevier, 2024)
In the rapidly evolving field of 2D materials, transition metal dichalcogenides (TMDs) have emerged as compelling candidates for electronic applications. This study investigates the electronic structure of the Hphase monolayer VS2 belonging to TMD family and the influence of strain on its band structure through Density Functional Theory (DFT). We employ two different pseudopotential approximations and a suite of computational methods including DFT+U, GAUPBE, G0W0, and self-GW to provide a nuanced understanding of its electronic band structure. A highlight of the study is its focus on how both uniaxial and biaxial strains, ranging from -5% to +5%, affect the electronic properties of the H -phase monolayer VS2. Our comprehensive analysis reveals that these tensile strains significantly widen the energy gap, with uniaxial strains having a more pronounced effect than their biaxial counterparts. Additionally, we identify an intriguing phase transition from a semiconducting to a metallic state under compressive strains, this transition is attributed to both symmetry breaking and bond length variation in the uniaxial case, the bond length in biaxial. These key findings not only enrich our understanding of the intricate electronic behavior of monolayer VS2 under different strains but also pave the way for the design of innovative electronic devices using strain engineering.
Keywords: 2D materials; Transition metal dichalcogenides (TMDs); Magnetic semiconductors; Electronic phase transitions; Strain engineering; Monolayer VS2